Factors Predicting Self-Management Behaviors Among Person with Chronic Kidney Disease Undergoing Continuous Ambulatory Peritoneal Dialysis - uparapho, sirirat; Soivong, Pratum; Tachaudomdach, Chiraporn (NU Journal of Nursing and Health Sciences, 2023)
This predictive research aimed to determine factors influencing the self-management behavior of persons with chronic kidney disease undergoing continuous peritoneal dialysis. Ninety participants included 65 persons receiving service at the outpatient department of the peritoneal dialysis clinic at the university hospital and 25 persons receiving service at the private peritoneal dialysis clinic. Research instruments are 1) a personal data record form, 2) a health literacy assessment form; 3) a social support assessment form; 4) the hospital anxiety and depression scale; and 5) a self-management behaviors questionnaire for persons with chronic kidney disease receiving continuous peritoneal dialysis. The psychometric properties of these instruments were approved. The scale-level content validity index/universal agreement of self-management behaviors was .90. Alpha Cronbach coefficients of the health literacy assessment form, social support assessment form, and the hospital anxiety and depression scale were .83, .96, .83, respectively. Test-retest was used to test the reliability of the self-management behavior questionnaire, and the correlation coefficient was .88. Data was collected from May 2022 to October 2022. Data analysis was descriptive statistics and multiple regression.The results revealed that most participants demonstrated an overall score of self-management behavior at a good level ( X- = 151.60, S.D. = 8.04). A group that has social support and depression predicted 17% of the self-management behavior. However, health literacy did not predict self-management. The results of this research demonstrated these two factors influencing overall self-management. Therefore, healthcare providers should enhance enough social support and prevent depression among this population. However, these factors predicted self-management at a low percentage. Therefore, further studies should explore other factors predicting self-management among persons with chronic kidney disease undergoing continuous ambulatory peritoneal dialysis.